2009
DOI: 10.1039/b814978j
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of ionic liquids in translucent tin dioxide monoliths by sol–gel processing

Abstract: SnO2 translucent monolith ionogels were obtained by a sol-gel processing using bis(2-methylbutan-2-oxy)di(pentan-2,4-dionato)tin as a precursor in the presence of various ionic liquids: [BMI][Br], [BMI][TFSI], [BMI][BF4]. The confinement of ionic liquids within the gels was evidenced by Differential Scanning Calorimetry, FTIR and FT-Raman spectroscopy. The ionic liquids could be efficiently washed off, which resulted in supermicroporous solids. Calcination in air at 550 degrees C of the dried monoliths resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 56 publications
0
42
0
1
Order By: Relevance
“…In a recent work, we explored a quite different approach, using a b-diketonato stabilized tin precursor to produce translucent monolith ionogels. A major advantage over the previous results was the possibility to use a wide range of IL ([C 4 [66].…”
Section: Gels From Metal Alkoxidesmentioning
confidence: 90%
“…In a recent work, we explored a quite different approach, using a b-diketonato stabilized tin precursor to produce translucent monolith ionogels. A major advantage over the previous results was the possibility to use a wide range of IL ([C 4 [66].…”
Section: Gels From Metal Alkoxidesmentioning
confidence: 90%
“…[56][57][58][59] Studies on the effect of confinement on melting point of ionic liquids has only started recently. [41][42][43] Detailed studies of silica porous matrix containing IL has been reported by Gçbel and co-workers [44] Table 2) which decreases to 8.5 8C and 8.3 8C for IL confined in silica pores of sizes 5.4 nm and 1.6 nm respectively. There is a decrease of~2 8C in m.p.…”
Section: Change In Melting Point On Confinementmentioning
confidence: 90%
“…The confinement of many ILs has been found to result in changes in the thermal properties (like melting point) as studied by differential scanning calorimetry (DSC). [41][42][43] Recently, Gçbel et al [44] have studied the DSC, NMR and IR spectra obtained from inserting 4 ] etc) in silica of different pore sizes, which was achieved by varying base catalysts like pyridine, 3-fluoropyridine and 2-picoline. More recently Gçbel et al [45] obtained IL-silica monoliths of different pore sizes by functionalizing the silica pore walls by adding N,N-dimethyl-pyridine-4-yl-(3-triethoxysilylpropyl)-ammonium iodide and 3-fluoropyridine and 2-(4-pyridylethyl)triethoxysilane in TMOS in different ratios.…”
mentioning
confidence: 99%
“…If the materials are dried using supercritical CO 2 (scCO 2 ), they are called aerogels. Recently ionic liquids have also been used during drying and calcination procedures, and the materials are then called ionogels [20]. …”
Section: Synthesis Of Monolithic Materialsmentioning
confidence: 99%
“…The resulting porous metal had macropores with a diameter of 600 nm [110]. Bellayer et al also utilized ionic liquids as the solvent in the sol-gel synthesis of SnO 2 monoliths [20]. Smått et al [42,104] applied the replica method to prepare manganium, cobalt and tin oxide cylindrical shape monoliths (dimensions circa 10 × 5 × 5 mm) by imbibing monolithic silica matrices with a saturated solution of the relevant inorganic salts.…”
Section: Monolithic Oxidesmentioning
confidence: 99%